Beyond Memorization: Pendekatan Deep Learning untuk Literasi dan Numerasi di Pendidikan Anak Usia Dini - Hastuti, Rochmi; Vemmi Kesuma Dewi, Raden Roro; Rahmianti, Siti (Khidmatussifa: Journal of Islamic Studies, 2025)
Early childhood learning is often focused on memorization and repetition activities, which tend to be shallow and provide limited space for the development of critical thinking. In the 21st-century education era, the deep learning approach offers a strategic alternative to foster meaningful literacy and numeracy skills in young children. This article aims to examine the application of deep learning in the context of Early Childhood Education (ECE), particularly in enhancing basic literacy and numeracy abilities. Through literature review and analysis of various learning practices in early childhood institutions, it is found that deep learning can be integrated through guided play strategies, structured exploration, reflective dialogue, and concept connections that align with children's developmental stages. This approach has been proven to increase active engagement, strengthen conceptual understanding, and develop children's cognitive potential from an early age. The article recommends that ECE teachers begin to shift the learning paradigm from rote memorization to meaningful, contextual, and enjoyable learning experiences. Keywords: Deep Learning, Early Childhood Education, Literacy, Numeracy, Meaningful Learning